Bioreactor-grown exo- and endo-β-glucan from Malaysian Ganoderma lucidum: An in vitro and in vivo study for potential antidiabetic treatment - Abdullah, Nur Raihan; Mohd Nasir, Mohd Hamzah; Azizan, Nur Hafizah; Wan-Mohtar, Wan Abd Al Qadr Imad; Sharif, Faez (Frontiers in Bioengineering and Biotechnology, 2022)
This study aims to identify the roles of exo-β-glucan (EPS-BG) and endo-β-glucan (ENS-BG) extracted from Ganoderma lucidum (GL) in inhibiting the alpha-glucosidase enzyme, a target mechanism for postprandial hyperglycaemia regulation. Upscale production of GL was done using a 10L bioreactor. The zebrafish embryo toxicity test (ZFET) was carried out based on OECD guidelines. The hatching rate, survival rate, heart rate, morphological malformation, or teratogenic defects were observed and determined every 24 h from 0-120 hours of post-exposure (hpe). For diabetes induction, the adult zebrafish (3–4 months of age) were overfed and induced with three doses of 350 mg/kg streptozotocin (STZ) by intraperitoneal injection (IP) on three different days (Day 1, 3, and 5). Oral sucrose tolerance test (OSTT) and anti-diabetic activity of EPS-BG and ENS-BG were evaluated (Day 7) using the developed model (n = 15). This study showed that EPS is the most potent compound with the highest inhibitory effect towards alpha-glucosidase enzyme with an IC50 value of 0.1575 mg/mL compared to ENS extracts (IC50 = 0.3479 mg/mL). Both EPS-BG and ENS-BG demonstrated a strong inhibition towards alpha-glucosidase activity similar to the clinically approved alpha-glucosidase inhibitor, acarbose (IC50 = 0.8107 mg/mL). ENS-BG is non-toxic towards zebrafish embryos with LC50 of 0.92 mg/mL and showed no significant changes in ZE hatching and normal heart rate as compared to untreated embryos (161 beats/min). Teratogenic effects of ENS-BG (<1.0 mg/mL) on zebrafish embryonic development were not observed. The DM model of zebrafish were acquired after the third dose of STZ with a fasting BGL of 8.98 ± 0.28 mmol/L compared to the normal healthy group (4.23 ± 0.62 mmol/L). The BGL of DM zebrafish after 30 minutes treated with EPS-BG and ENS-BG showed a significant reduction (P<0.0001). Both EPS-BG and ENS-BG significantly reduced DM zebrafish's peak blood glucose and area under the curve (AUC) in OSTT. Hence, EPS-BG and ENS-BG extracted from GL showed promising inhibition of the alpha-glucosidase enzyme and are considered non-toxic in ZE. Moreover, EPS-BG and ENS-BG reduced blood glucose levels and inhibited hyperglycaemia in DM zebrafish.